2021
DOI: 10.1094/phytofr-08-20-0011-r
|View full text |Cite
|
Sign up to set email alerts
|

Role and In Vivo Localization of Fusarium oxysporum f. sp. strigae and Bacillus subtilis in an Integrated Striga hermonthica Biocontrol System

Abstract: To improve the efficiency of Striga hermonthica biological control in the context of an integrated biocontrol system, the role/impact of coinoculating the mycoherbicide Fusarium oxysporum f. sp. strigae (Fos) with a plant growth promoting rhizobacterium, Bacillus subtilis isolate GB03, on S. hermonthica attachment and sorghum biomass was investigated. Fos isolates (Foxy-2, FK3) and GB03, including Trichoderma viride (IMB12098 strain) as reference, were applied as single and combined treatments to S. hermonthic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Sorghum (Sorghum bicolor L. Moench) seeds (cultivar PI563294) were sampled from Maradi, Niger. Our previous research studies confirmed the susceptibility of this sorghum cultivar to S. hermonthica [5,6]. The S. hermonthica and sorghum seeds were separately surface-sterilized using sodium hypochlorite, Tween 20 ® and double distilled water (ddH 2 O), then air-dried, according to the procedure of Anteyi and Rasche [5,6].…”
Section: Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…Sorghum (Sorghum bicolor L. Moench) seeds (cultivar PI563294) were sampled from Maradi, Niger. Our previous research studies confirmed the susceptibility of this sorghum cultivar to S. hermonthica [5,6]. The S. hermonthica and sorghum seeds were separately surface-sterilized using sodium hypochlorite, Tween 20 ® and double distilled water (ddH 2 O), then air-dried, according to the procedure of Anteyi and Rasche [5,6].…”
Section: Methodsmentioning
confidence: 63%
“…strigae (Fos) is a well-known bioherbicide (mycoherbicide), that has proven effective for controlling parasitic Striga spp., under both natural and artificial environments [52,58,64]. Although, various Fos isolates with significant pathogenicity towards S. hermonthica have been reported [82], in some cases, the bioherbicidal effectiveness of Fos isolates against S. hermonthica has shown to be inconsistent [6,7,76]. The inconsistent effectiveness of Fos isolates against differing S. hermonthica populations is, amongst others, a major challenge that deters the widespread application of any bioherbicide against its target weed [18,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMF enhance cereal growth to withstand Striga damage and facilitate host plant's uptake of micronutrients, water, and phosphorus (P) from soil through extraradical fungal hyphae (Olowe et al, 2018). The strigolactones (SLs) exudation by the host in the soil is ultimately reduced by the increased uptake of P via symbiotic interactions by AM fungi, thereby reducing Striga infection (Aquino et al, 2021). Furthermore, rate of Striga infestation is equally lowered by the soil microbes through their release of amino acids such as methionine or by the producing secondary metabolites such as trichothecenes which may interfere with SL perception.…”
Section: Current Trends In Striga Managementmentioning
confidence: 99%